Microstructures and improved Jc–H characteristics of Cl-containing YBCO thin films prepared by the fluorine-free MOD method. (1st December 2015) - Motoki, Takanori; Shimoyama, Jun-ichi; Ogino, Hiraku; Kishio, Kohji; Roh, Jiyoung; Tohei, Tetsuya; Ikuhara, Yuichi; Horii, Shigeru; Doi, Toshiya; Honda, Genki; Nagaishi, Tatsuoki
Abstract: Undoped, Cl-doped, (Cl, Hf) co-doped and (Cl, Sn) co-doped YBa2 Cu3 O y (YBCO) thin films have been prepared by the fluorine-free metal–organic decomposition (FF-MOD) method on SrTiO3 (100) single-crystalline substrates. Cross-sectional microstructures of these films were investigated in detail using scanning transmission electron microscopy (STEM). Rectangular-shaped oxychloride precipitates (Ba2 Cu3 O4 Cl2 ) and fine particles (BaSnO3 ) were clearly observed in the (Cl, Sn) co-doped films. The magnetic angular dependence of the critical current density ( J c – H – θ ) of these films was evaluated. The existence of c -axis-correlated type pinning centers was suggested in Cl-containing YBCO films, whereas this type of pinning is not common in MOD-processed films. J c values were enhanced by Cl doping and further by (Cl, Sn) co-doping in all magnetic field directions at 77 K. This improved J c – H – θ property with c -axis-correlated pinning sites is the first report in FF-MOD-processed YBCO films.